Investigation of dormancy in acute myeloid leukaemia cells and the induction of dormancy in their response to genotoxic stress - Al-Asadi, Mazin Gh. (2017)
Cancer cells can exist in a reversible state of dormancy (G0 phase of the cell cycle). Relapse of acute myeloid leukaemia (AML) is likely due to dormant cells escape frontline treatment. Dormant AML cells have been identified in the bone marrow (BM) endosteal region which is characterised by an excess of TGFβ1 and a shortage of nutrients.